Hambatan Pelaksanaan Eksekusi Putusan Perdata dan Upaya Penyelesaiannya dalam Praktik Peradilan di Indonesia - Zahra Najwa Herlita; Putri Rahayu; Anggi Sri Haryati Simasmata (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the obstacles to the implementation of civil judgment execution and efforts to resolve them in judicial practice in Indonesia. The research method used is normative juridical legal research with a statutory and conceptual approach. The data used is secondary data obtained through literature study, which is then analyzed qualitatively. The results of the study indicate that the implementation of civil judgment execution still faces various obstacles, which include legal, technical, and non-legal obstacles. Legal obstacles include legal efforts used to delay execution, technical obstacles related to the unclear object of the dispute and limited facilities, while non-legal obstacles include resistance from the losing party and the public. These conditions indicate ineffectiveness in the implementation of civil procedural law, resulting in the failure to achieve legal certainty, justice, and benefit. Efforts to resolve obstacles are carried out through improving regulations, increasing the professionalism of judicial officials, utilizing technology, and a non-litigation approach. Thus, legal reform and strengthening of judicial institutions are needed so that the implementation of civil judgment execution can run more effectively and provide optimal legal protection.